KONSEPSI PENDIDIKAN ISLAM DALAM MENINGKATKAN KUALITAS SUMBER DAYA MANUSIA - A SURADI (Jurnal Pendidikan Islam, 2018)
In terms of human resource development, education has a strategic value and an important role as people investment in the future. Theoretically, education is the basis of economic growth, the basis of the development of science and technology, eradicating the poverty and income gap, and improving the welfare and quality of civilization in general. This general strategic value of education, concludes that education holds tremendous power to create an overall environmental aspect and can provide the most valuable information about future grips and help students to prepare essential living needs to anticipate the changes.